A study of anemia among adolescent girls in eastern part of Nepal - Kanodia, Piush; Bhatta, Mukesh; Singh, Rupa Rajbhandari; Bhatta, Nisha K; Shah, Gauri Shankar (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Anemia is a global health problem. About 40% of the world's population suffers from anemia and adolescence is one of the most vulnerable age group. Hence the objective of the study was to determine prevalence and distribution of anemia among adolescent girls in eastern part of Nepal. Materials & Methods: This cross sectional study was conducted in a Government School of Dharan over a period of one year. There were total 433 participants, whose clinical and demographic profile were recorded and analyzed. Hemoglobin estimation was done by using cyanmethaemoglobin method and anemia was defined as per WHO cut-off. Results: The overall prevalence of anemia was found to be 51.3%. Prevalence was significantly more in pre-menarche age and undernourished girls (p<0.05). However factors like diet (vegetarian/non-vegetarian), worm infestation and parental education did not have a significant impact on occurrence of anemia. Conclusion: Anemia is the major health problem among adolescent girls in eastern part Nepal with high prevalence rate and nutrition is one of the leading causative factors for anemia. JCMS Nepal. 2016;12(1):19-22.